Agricultural Engineering Laboratory (1943)
Exterior view of the U.S.D.A.'s Agricultural Engineering Laboratory located in Beltsville, Maryland. The laboratory was predominately used for practical investigations related to plants and fertilizers in support of the work of the Fixed Nitrogen Research Laboratory located in Washington, D.C.
Keywords: Nitrogen fertilizer industry; United States. Bureau of Chemistry and Soils; United States. Department of Agriculture